Generating lower ethanol yields in fermentations by Saccharomyces cerevisiae via diversion of carbon flux towards the production of fructo-oligosaccharides - Brandt, Bianca Anina (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.